Implementation Of Performance Achievements Of The Mangkang Terminal Semarang City - Nashrullah Nashrullah; Ika Utami Yulihapsari (International Journal of Economics and Management Sciences, 2024)
The growth in population and the usage of private automobiles in Semarang City have an impact on the operation and performance of the Mangkang Terminal with Type A, namely the terminal's class, service evaluation, and performance. The purpose of this study is to identify terminal class criteria, service enhancements, and operational performance that requires improvement at the Semarang Terminal. For this reason, the terminal class is created in accordance with rules governing technical guidelines for defining terminal class criteria, and service and terminal performance are assessed using the IPA method. A Google form with as many questions regarding services as an evaluation of satisfaction and interest is issued to terminal users, with the primary goal of improving and determining terminal class being to identify 5 indications that are tailored to current circumstances. According to the findings of the terminal class study, the Semarang Terminal is in class 1, which is the highest priority for developing and delivering services to road passenger terminals.